Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1590/s0102-79722013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Inteligência, habilidades sociais e expectativas acadêmicas no desempenho de estudantes universitários

Abstract: Resumo AbstractThis study aimed to assess the variables that could affect academic performance by studying correlations between intelligence, social skills, and academic expectations and how such factors affect academic performance of university students in their fi rst year in college. The sample consisted of 196 students (156 women and 40 men) aged from 17 to 59. Abstract Reasoning (BPR-5s) tests, the Social Skills Inventory (IHS-Del-Prette), and the Academic Involvement Questionnaire (AIQ) -Expectations ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
1
54

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 14 publications
0
15
1
54
Order By: Relevance
“…As verified, most studies on this theme had correlational designs (Artino et al, 2012;Fernandez et al, 2012;Nuñez Del Arco, 2005;Oyarzún Iturra, 2012;Victoroff & Boyatzis, 2013), while only the studies by Gomes and Soares (2013) and Ihm et al (2013) used predictive methods. Ihm et al (2013) adopted social skills and academic performance measures at different moments in the course and Gomes and Soares (2013) assessed only the start of the course, indicating the need for further research on the temporal scope of the relations between the social skills repertoire and academic performance.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…As verified, most studies on this theme had correlational designs (Artino et al, 2012;Fernandez et al, 2012;Nuñez Del Arco, 2005;Oyarzún Iturra, 2012;Victoroff & Boyatzis, 2013), while only the studies by Gomes and Soares (2013) and Ihm et al (2013) used predictive methods. Ihm et al (2013) adopted social skills and academic performance measures at different moments in the course and Gomes and Soares (2013) assessed only the start of the course, indicating the need for further research on the temporal scope of the relations between the social skills repertoire and academic performance.…”
mentioning
confidence: 95%
“…Some studies indicate a positive relation between a good social skills repertoire and satisfactory academic performance (Aguilar, 2008;Artino et al, 2012;Fernandez et al, 2012;Oyarzún Iturra et al, 2012;Victoroff & Boyatzis, 2013). In the study by Nuñez Del Arco (2005), no significant correlation as identified between these variables and Gomes and Soares (2013) identified that the relation between social skills and academic performance varied according to specific social skills factors. Students with higher mean scores in the factor Coping and Self-assertion with risk obtained higher mean academic performance scores, while students with higher mean scores in the factor Conversation obtained lower mean academic performance scores.…”
mentioning
confidence: 96%
See 3 more Smart Citations